Rancang Bangun dan Pengujian Performa Mesin Pembubur Sampah Organik Menjadi Pakan Maggot Kapasitas 24 kg/jam - Budi Triyono; Raden Roro Yngwistian Jannavis Astie; Zainuddin; Dibyo Setiawan; Apri Setiawan (Infotekmesin, 2025)
Organic waste management, particularly from canteens or kitchens, which often consists of leftover meat, fish, and vegetables, remains a significant challenge. If processed properly, this waste has the potential to be used as maggot feed. To process this organic waste, it is necessary to develop an organic waste slurry machine designed to process organic waste from the Pujasera or campus canteen into maggot feed. The development process for this machine includes six stages: Planning, Conceptual design, Detailed design, Technical documentation, Manufacturing and assembly, and Testing. From these stages, a compact organic waste slurry machine is produced with dimensions of 815 x 425 x 840 mm, driven by a 1-phase electric motor with a power of 1.5 HP (1,100 Watts) and a rotation speed of 1,050 RPM. The test results show that this machine is effective in shredding organic waste with a capacity of 24 kg/hour, a maximum power of 1,037 Watts, and an energy consumption of 0.860 kWh. These results provide an innovative and economical solution, promoting the use of organic waste as a valuable resource.